A review of graphene-based nanomaterials for removal of antibiotics from aqueous environments. (October 2019) - Wang, Xuandong; Yin, Renli; Zeng, Lixi; Zhu, Mingshan
Abstract: Antibiotics as emerging pharmaceutical pollutants have seriously not only threatened human life and animal health security, but also caused environmental pollution. It has drawn enormous attention and research interests in the study of antibiotics removal from aqueous environments. Graphene, an interesting one-atom-thick, 2D single-layer carbon sheet with sp 2 hybridized carbon atoms, has become an important agent for removal of antibiotic, owing to its unique physiochemical properties. Recently, a variety of graphene-based nanomaterials (GNMs) are reported to efficiently remove antibiotics from aqueous solutions by different technologies. In this review, we summarize different structure and properties of GNMs for the removal of antibiotics by adsorption. Meanwhile, advanced oxidation processes (AOPs), such as photocatalysis, Fenton process, ozonation, sulfate radical and combined AOPs by the aid of GNMs are summarized. Finally, the opportunities and challenges on the future scope of GNMs for removal of antibiotics from aqueous environments are proposed. Graphical abstract: Image 1 Highlights: Antibiotics are as emerging pharmaceutical pollutants in aqueous environment. Graphene-based material has high adsorption capacity and oxidation ability. Adsorption and advanced oxidation processes are used for removal of antibiotics. Abstract : Capsule: Owing to high adsorption capacity and oxidation ability of the graphene-based nanomaterials, a timely review for their in the removal of antibiotics is urgent need.